UNGKAPAN KEPERCAYAAN MASYARAKAT PETANI GAMBIR DI KENAGARIAN SIMPANG KAPUAK KECAMATAN MUNGKA KABUPATEN 50 KOTA - Taufik Hidayat; Harris Effendi Thahar; Zulfikarni Zulfikarni (Jurnal Bahasa dan Sastra, 2013)
This observation was written to (1)  described the category of the expression of gambier farmers in Kenagarian Simpang Kapuak Kecamatan Mungka Kabupaten 50 Kota (2) described the meaning contained in the expression of gambier farmers in Kenagarian Simpang Kapuak Kecamatan Mungka Kabupaten 50 Kota (3) described the function of the expression of gambier farmers in Kenagarian Simpang Kapuak Kecamatan Mungka Kabupaten 50 Kota. The sources of this study is oral sources that expressed by informants who have been determined. Data were collected by doing some interview and record all phrased that noticed by the informant. The results of the observation are 49 expressions. That Expression consists of the human body categories and folkmedicine, homeand domestic work, livelihoods and social relations, travel and transportation,death and funeral customs. The meaning of the expression is implicitly.  The Function of the expressionis to tell, to educate, to warn, to ban and to entertain.   Kata kunci: ungkapan, kepercayaan, masyarakat, petani, gambir.